Atuação de enfermeiras da Estratégia Saúde da Família na atenção à saúde LGBT+ - Paiva, Ariane Tufaile de (Universidade Federal de São Carlos, 2023)
To analyze the performance of nurses from the Family Health Strategy in health care for LGBT+ people. Methods: Qualitative study based on Institutional Analysis. Data were collected in August 2021 through semi-structured interviews carried out with 14 nurses from the Family Health Strategy in municipalities in the State of São Paulo. They were processed by the IRaMuTeQ® software and worked through lexical analysis. Results: The textual corpus gave rise to three themes, which address the nurses' practice, the difficulties and challenges they experience in caring for LGBT+ people and the direct association of LGBT+ people with sexually transmitted infections. Final Considerations: Lack of preparation, access to information and the development of expanded listening are still gaps in the performance of nurses from the Family Health Strategy in caring for LGBT+ people, but welcoming and bonding have been bets to bring nursing care closer to people LGBT+.
Role of nurses from the Family Health Strategy in LGBT+ health care
Keywords: Enfermagem; Atenção primária à saúde; Saúde pública; Minorias sexuais e de gênero; Sexualidade; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA